2017
DOI: 10.1161/circulationaha.117.029190
|View full text |Cite
|
Sign up to set email alerts
|

Lower Risk of Heart Failure and Death in Patients Initiated on Sodium-Glucose Cotransporter-2 Inhibitors Versus Other Glucose-Lowering Drugs

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
316
2
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(365 citation statements)
references
References 37 publications
28
316
2
19
Order By: Relevance
“…11, 12, 22, 23, 24, 25, 26, 27, 28, 29, 30 For cardiovascular outcomes analysis, 3 RCTs11, 12, 22 and 2 observational studies23, 24 were included with 351 476 patients and median follow‐up of 3.1 years. Nine RCTs contributed to the analysis of long‐term noncardiovascular safety and efficacy of SGLT2 inhibitors, with a medium follow‐up of 2 years 11, 12, 22, 25, 26, 27, 28, 29, 30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11, 12, 22, 23, 24, 25, 26, 27, 28, 29, 30 For cardiovascular outcomes analysis, 3 RCTs11, 12, 22 and 2 observational studies23, 24 were included with 351 476 patients and median follow‐up of 3.1 years. Nine RCTs contributed to the analysis of long‐term noncardiovascular safety and efficacy of SGLT2 inhibitors, with a medium follow‐up of 2 years 11, 12, 22, 25, 26, 27, 28, 29, 30.…”
Section: Resultsmentioning
confidence: 99%
“…All trials were carried out with patients who had type 2 DM. Empagliflozin was used in 2 trials,11, 29 canagliflozin was used in 4 trials,12, 26, 27 and dapagliflozin was used in 3 trials25, 28, 30; the 2 observational studies involved various SGLT2 inhibitors 23, 24. All studies were multicenter, performed across multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these patients were not at increased CV risk (only 13% had established CV disease). In this propensity‐matched PER using data from medical claims, primary care/hospital records, and national registries in six countries (the United States, Germany, Sweden, Norway, Denmark and the UK), the authors assessed the risks of hospitalization for heart failure (HHF), death, and the combined endpoint of heart failure hospitalization or death, which were all lower in patients receiving an SGLT2‐I, without significant heterogeneity across countries and with consistent results among multiple sensitivity analyses 10. In particular, the pooled analysis of all‐cause death using patient data from five of the countries (this information was not available for the German registry) showed a 51% reduction favouring patients with SGLT2‐Is (0.49; 0.41–0.57; without significant heterogeneity among SGLT2‐Is).…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…When a sufficient overlap between patient groups exists,8 PSM can generate quasi‐experimental comparisons that make retrospective studies closer to RCTs. For instance, 2 RCTs indicate that SGLT2 inhibitors improve cardiovascular outcomes in patients with T2D and high risk for or established cardiovascular disease9, 10 and 2 retrospective studies on administrative databases have confirmed these findings in broader T2D patient populations 11, 12…”
Section: Introductionmentioning
confidence: 99%